1993
DOI: 10.3109/00365529309098294
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Cell Antibodies among Peruvians with Gastric Pathologic Changes

Abstract: Parietal cell antibodies were present in 12% of 272 Peruvians presenting for endoscopy. Gender, age, socioeconomic status, ethnic background (Peruvian versus Japanese), and altitude at which the patient lived were not associated with the presence of parietal cell antibodies. No significant relationship could be shown between the presence of parietal cell antibodies and either Helicobacter pylori infection or gastric lesions, including chronic atrophic gastritis. Loss of proper gastric glands was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…We did not find a statistically significant association between GA and antiparietal cell antibodies in this study, and this is in keeping with the work of Kohlstadt et al [27] who found that these antibodies are unrelated to Hp infection and the pathological changes associated with it.…”
Section: Discussionsupporting
confidence: 80%
“…We did not find a statistically significant association between GA and antiparietal cell antibodies in this study, and this is in keeping with the work of Kohlstadt et al [27] who found that these antibodies are unrelated to Hp infection and the pathological changes associated with it.…”
Section: Discussionsupporting
confidence: 80%
“…On these bases, it may be suggested that in some patients, H. pylori infection per se may induce a parietal damage with consequent autoimmune responses. The former hypothesis is supported further by studies in Peruvians with gastric pathological changes, wherein was found a 12% prevalence of PCAs unrelated to any specific gastric disease [33].…”
Section: Discussionmentioning
confidence: 69%
“…A correlation between H. pylori and gastric antibodies has been reported in some [21][22][23][24][25] but not all studies. 15,54 We observed an association between H. pylori and PCA when the cut-off point of PCA-positivity was ‡ 1/20, but not anymore when it was ‡ 1/40, suggesting that low PCA titres might reflect H. pylori infection. The HLA-bound susceptibility to H. pylori infection and to PCA differed in this study.…”
Section: Histological Datamentioning
confidence: 73%
“…Cohort follow‐up studies have suggested a 0.3–2% annual increase of atrophic corpus gastritis in subjects with H. pylori ‐positive gastritis 14 , . 52 , 53 However, others have found no or a negative link between H. pylori and atrophic corpus gastritis, 15 , 44 , 54 and earlier studies, for historical reasons, did not report the H. pylori status 55 , . 56 We observed no association between H. pylori status and pre‐atrophic autoimmune gastritis, when the mucosa is still hospitable for H. pylori , and we identified PCA and gastrin as risk markers for autoimmune gastritis.…”
Section: Discussionmentioning
confidence: 96%